High energy efficiency for low error rate in wireless relay networks. Issue 5 (1st July 2018) - Khalil, Muhammad; Barber, Stevan; Sworby, Kevin
Abstract : A new method to increase energy efficiency (EE) and decrease bit error rate (BER) in amplify‐and‐forward (AF) relay networks is presented in this study. In this network, the source transmitted signal through flat fading channel to a set of intermediate relay nodes which amplify and then forward the signal to the destination through a set of independent flat fading channels. The proposed EE is derived in a balanced scheme with spectral efficiency (SE), when relay nodes locations are taken into consideration. This balance between EE and SE is achieved by minimising power consumption. The BER for this balance is analysed and the relationship between BER and EE is derived. All analytical expressions are validated by numerical analysis and simulation. It is found that only a small increase in EE leads to a reduction in BER.